PUG-View: programmatic access to chemical annotations integrated in PubChem - Sunghwan Kim; Paul A. Thiessen; Tiejun Cheng; Jian Zhang; Asta Gindulyte; Evan E. Bolton (Journal of Cheminformatics, 2019)
Abstract PubChem is a chemical data repository that provides comprehensive information on various chemical entities. It contains a wealth of chemical information from hundreds of data sources. Programmatic access to this large amount of data provides researchers with new opportunities for data-intensive research. PubChem provides several programmatic access routes. One of these is PUG-View, which is a Representational State Transfer (REST)-style web service interface specialized for accessing annotation data contained in PubChem. The present paper describes various aspects of PUG-View, including the scope of data accessible through PUG-View, the syntax for formulating a PUG-View request URL, the difference of PUG-View from other web service interfaces in PubChem, and its limitations and usage policies.